A (Un)Pleasant Arithmetic of Fiscal Policy: the Case of Italian Public Debt - Luigi Marattin; Massimiliano Marzo (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2008)
Using the simple arithmetic of government budget constraint, we perform an analysis on the Italian case, investigating the consequences on the main public finance aggregates of the adoption of a fiscal policy rule responding to past real debt/GDP ratio. Such a rule, firmly grounded in the economic analysis, would allow the reduction of Italy's outstanding stock of debt without requiring the strict adherence to the 3% criterion for deficit/GDP ratio, as prescribed by SGP. We perform a forecasting exercise under five alternative scenarios, analyze the details of a structural debt reduction strategy with alternative yearly step, and finally carry out a counterfactual exercise by applying our proposed rule to the period 1994-2006.
Keywords: 330